Altered local and systemic immune profiles underlie lymph node metastasis in breast cancer patients. Issue 11 (26th November 2012) - Zuckerman, Neta S.; Yu, HongXiang; Simons, Diana L.; Bhattacharya, Nupur; Carcamo‐Cavazos, Valeria; Yan, Ning; Dirbas, Frederick M.; Johnson, Denise L.; Schwartz, Erich J.; Lee, Peter P.
Abstract Cancer‐mediated immune dysfunction contributes to tumor progression and correlates with patient outcome. Metastasis to tumor draining lymph nodes (TDLNs) is an important step in breast cancer progression and is used to predict patient outcome and survival. Although lymph nodes are important immune organs, the role of immune cells in TDLNs has not been thoroughly investigated. We hypothesized that the host immune response in node negative (NN) patients is more intact and thereby can resist tumor invasion compared to node positive (NP) patients. As such, lymph node metastasis requires breakdown of the host immune response in addition to escape of cancer cells from the tumor. To investigate the immunological differences between NN and NP breast cancer patients, we purified and profiled immune cells from the three major compartments where cancer and immune cells interact: tumor, TDLNs and peripheral blood. Significant down‐regulation of genes associated with immune‐related pathways and up‐regulation of genes associated with tumor‐promoting pathways was consistently observed in NP patients' TDLNs compared to NN patients. Importantly, these signatures were seen even in NP patients' tumor‐free TDLNs, suggesting that such immune changes are not driven solely by local tumor invasion. Furthermore, similar patterns were also observed in NP patients' tumor and blood immune cells, suggesting that immunological differences between NN and NP patients are systemic. Together, these findings suggest that alterations in overall immune function may underlie risk for LN metastasis in breast cancer patients.